A prospective study of ripple mapping the post-infarct ventricular scar to guide substrate ablation for ventricular tachycardia - Luther,V; Linton,NW; Jamil-Copley,S; Koa-Wing,M; Lim,PB; Qureshi,N; Ng,FS; Hayat,S; Whinnett,Z; Davies,DW; Peters,NS; Kanagaratnam,P (Circulation: Arrhythmia and Electrophysiology, 2016)
BACKGROUND: Post-infarct ventricular tachycardia is associated with channels of surviving myocardium within scar characterized by fractionated and low-amplitude signals usually occurring late during sinus rhythm. Conventional automated algorithms for 3-dimensional electro-anatomic mapping cannot differentiate the delayed local signal of conduction within the scar from the initial far-field signal generated by surrounding healthy tissue. Ripple mapping displays every deflection of an electrogram, thereby providing fully informative activation sequences. We prospectively used CARTO-based ripple maps to identify conducting channels as a target for ablation. METHODS AND RESULTS: High-density bipolar left ventricular endocardial electrograms were collected using CARTO3v4 in sinus rhythm or ventricular pacing and reviewed for ripple mapping conducting channel identification. Fifteen consecutive patients (median age 68 years, left ventricular ejection fraction 30%) were studied (6 month preprocedural implantable cardioverter defibrillator therapies: median 19 ATP events [Q1-Q3=4-93] and 1 shock [Q1-Q3=0-3]). Scar (<1.5 mV) occupied a median 29% of the total surface area (median 540 points collected within scar). A median of 2 ripple mapping conducting channels were seen within each scar (length 60 mm; initial component 0.44 mV; delayed component 0.20 mV; conduction 55 cm/s). Ablation was performed along all identified ripple mapping conducting channels (median 18 lesions) and any presumed interconnected late-activating sites (median 6 lesions; Q1-Q3=2-12). The diastolic isthmus in ventricular tachycardia was mapped in 3 patients and colocated within the ripple mapping conducting channels identified. Ventricular tachycardia was noninducible in 85% of patients post ablation, and 71% remain free of ventricular tachycardia recurrence at 6-month median follow-up. CONCLUSIONS: Ripple mapping can be used to identify conduction channels within scar to guide functional substrate